GERAKAN EKOPASTORAL DALAM SEMANGAT LAUDATO SI’ ORANG MUDA KATOLIK DI PAROKI ST. FRANSISKUS ASISI, KEUSKUPAN LABUAN BAJO - Widyawati, Fransiska; Dhongo, Maria Yohanista; Chen, Martinus (Lembaga Penelitian STKIP Widya Yuwana, 2025)
The Church bears a responsibility to address and prevent environmental crises, particularly through the implementation of ecopastoral initiatives. At the parish level, the involvement of Catholic Youth (Orang Muda Katolik-OMK) in ecopastoral activities is of paramount importance. This study examines the ecopastoral movement involving OMK in the Parish of St. Francis of Assisi, Diocese of Labuan Bajo. The primary research question is: How is the OMK movement engaged in ecopastoral efforts in the spirit of Laudato Si' within the Parish of St. Francis of Assisi? Utilizing a qualitative research method, data was collected through interviews, observations, and the analysis of parish documents. The findings of this study are threefold: (1) OMK plays a crucial role in the implementation of ecopastoral initiatives within the Parish of St. Francis of Assisi; (2) The OMK ecopastoral activities manifest in various forms, including strengthening the ecological character of young people, ecological diakonia, ecological kerygma, and ecological liturgy; (3) The spirit of Laudato Si' and the example set by Saint Francis of Assisi are significant influencing on the OMK ecopastoral movement in the parish. In conclusion, the OMK ecopastoral initiative has emerged as a positive movement within the church and parish, promoting environmental sustainability. This research recommends that the OMK ecopastoral movement be continued, strengthened, and expanded to other parishes and regions.